Progress in ICP-MS Analysis of Minerals and Heavy Metals in Traditional Medicine - Chen, Wanyue; Yang, Yichu; Fu, Ke; Zhang, Dewei; Wang, Zhang (Frontiers in Pharmacology, 2022)
Aim: The application of ICP-MS and its combined technology in the determination of mineral and heavy metal elements in medicinal materials derived from plants, animals and minerals and their preparations (Chinese patent medicine) as well as biological products was systematically reviewed. It provides a reference for improving the quality standard of traditional medicine and exploring the effective components, toxic components and action mechanism of traditional medicine. Materials and methods: Collected from PubMed, CNKI, Web of Science, VIP and other databases, 234 papers related to the determination of mineral and heavy metal elements in medicinal materials derived from plants, animals and minerals and their preparations (Chinese patent medicine) were classified and sorted by ICP-MS method. Conclusion: The application of ICP-MS in traditional Chinese medicine was the most, followed by Arabic medicine. ICP-MS was used to determine more medicinal materials derived from plants, and Cu was determined the most, and the characteristic inorganic element spectrum of medicinal materials can also be established. ICP-MS and its combined technology are widely used in Chinese patent medicine, but the test of biological samples is the least. The information provided in this paper can provide reference for improving the quality standard of traditional medicines and exploring the active ingredients and toxic ingredients and their mechanism of action.